PHYTOCHEMICAL ANALYSIS AND ICP-OES NUTRIMENTAL CONTENT IN EXTRACTS OF CASTOR-OIL PLANT (R. COMMUNIS), SWEET ACACIA (V. FARNESIANA) AND PINK GRASS (R. REPENS) - Alcantara, Alan Mendoza; Barajas, Sergio Gutiérrez; Cabrera, Braulio Edgar Herrera; Garciglia, Rafael Salgado; Padilla, Edgar Ayala; Valdez, Luis Germán López; Barrales-Cureño, Hebert Jair (Seven Editora, 2026)
In the present investigation, several specialized secondary metabolites were extracted and identified to combat entomological pests and the nutritional aspects of three plant species were analyzed. Three wild plants were evaluated: castor-oil plant (Ricinus communis), sweet acacia (Vachellia farnesiana) and pink grass (Rhynchelytrum repens). The pure extracts were evaluated with the following especiallized secondary metabolites analysis: flavonoids, sterols, triterpenes, phenols, quinones, saponins, catechins, tannins, triterpenes and anthocyanins. Macronutrient and micronutrient analyses of the extracts of the three plants extracts of castor-oil plant (Ricinus communis), sweet acacia (Vachellia farnesiana) and pink grass (Rhynchelytrum repens) were evaluated with the following methods. The Dumas method was used to analyze the percentage of nitrogen (w/w); the microwave ICP-OES (Inductively Coupled Plasma/Optical Emission Spectrophotometer) method was used to analyze the percentages of macronutrients in percentage (w/w) of phosphorus, potassium, calcium, magnesium, sulfur and sodium (mg/kg) and the percentage of chlorine with silver nitrate/argentometry. Micronutrient analyses of plant extracts were evaluated by microwave digestion/ICP-OES digestion in mg/kg of iron, zinc, manganese, copper, boron, nickel and molybdenum.